Pandemic of COVID 19 and old adults Brazilians: a reflection on social isolation, infoexclusion, infodemia and idadism - Alonso, Vanessa; Cipolli, Gabriela Cabett; Flauzino, Karina de Lima; Cachioni, Meire (Revista Kairós-Gerontologia, 2020)
The coronavirus disease 2019 (COVID-19) pandemic presents challenges to older people, especially those from low and middle income countries. Social distancing is one of the restrictive measures adopted to avoid contagion, which can which can trigger damages to physical and mental health to older adults. In addition to that, digital exclusion, infodemia and ageism are also present in this context. Digital access can assist older people in various aspects of life, including minimizing the negative consequences caused by social distancing. With the help of technology, educational measures have great potential to reduce the negative consequences of COVID-19 pandemic encouraging efforts to overcome the challenges that are posed to older adults.